FACTORS OF IMPROVEMENT OF PROFESSIONAL SKILLS OF THE FUTURE TEACHER OF FINE ARTS - IKROMOVA M.N. (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article talks about the combination of theoretical and practical knowledge in the professional training of future teachers of Fine Arts, the importance of performing theoretical and practical exercises of pencil drawing, which is the basis of Fine Arts, in the process of work. Students will be given practical advice on how to describe, depending on nature.